2022
DOI: 10.3389/fonc.2022.874457
|View full text |Cite
|
Sign up to set email alerts
|

The Chemopreventive Role of β-Elemene in Cholangiocarcinoma by Restoring PCDH9 Expression

Abstract: Backgroundβ-Elemene, an effective anticancer component isolated from the Chinese herbal medicine Rhizoma Zedoariae, has been proved to have therapeutic potential against multiple cancers by extensive clinical trials and experimental research. However, its preventive role in cholangiocarcinoma (CCA) and the mechanisms of action of β-elemene on CCA need to be further investigated.MethodsA thioacetamide (TAA)-induced pre-CCA animal model was well-established, and a low dosage of β-elemene was intragastrically (i.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…It is unclear whether patients with colorectal cancer could benefit from elemene treatment. Other nonindication uses of elemene, such as in pancreatic carcinoma and biliary tract cancer, have only been investigated in in vitro studies (Long et al, 2019;Wu et al, 2022). These findings indicated that efforts to reduce elemene use in patients without suitable indications should be made preferentially.…”
Section: Discussionmentioning
confidence: 99%
“…It is unclear whether patients with colorectal cancer could benefit from elemene treatment. Other nonindication uses of elemene, such as in pancreatic carcinoma and biliary tract cancer, have only been investigated in in vitro studies (Long et al, 2019;Wu et al, 2022). These findings indicated that efforts to reduce elemene use in patients without suitable indications should be made preferentially.…”
Section: Discussionmentioning
confidence: 99%
“…Through activating GSK-3β, PCDH9 prevents cell migration and the epithelial-mesenchymal transition in hepatocellular cancer (9). PCDH9 interacts with DNMT1, activated DNMT1 suppresses CDH2 and inhibit cancer metastasis (10).As a member of the epidermal growth factor (EGF) family, amphiregulin (AREG) is expressed in many different types of neoplasms, such as pancreatic, ovarian, breast, bladder, colon, and lung malignancies (11). Through the EGFR/PI3K/Akt/NF-κB signaling pathway, AREG increased the expression of ICAM-1 and accelerated cancer cell motility in osteosarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…Protocadherin 9 ( PCDH9 ) encodes a member of the protocadherin family, and cadherin superfamily, of transmembrane proteins containing cadherin domains. In some human diseases, PCDH9 is negatively correlated with the proliferation and apoptosis of tumor cells [ 49 ] and is also a target of some anticancer molecules [ 50 ]. In mouse nerves, PCDH9 is involved in the formation of specific neural circuits [ 51 ], while in chickens, only a specific spatiotemporal expression pattern of PCDH9 was found in chick’s embryonic spinal cords, suggesting that it can affect the development of the spinal cord and its surrounding tissues [ 52 ].…”
Section: Discussionmentioning
confidence: 99%